Staphylococcus and Streptococcus - Kırmusaoğlu, Sahra (IntechOpen, 2020)
Staphylococcus spp. and Streptococcus spp. have not only got pathogenic isolates, but also non-pathogenic isolates. Staphylococcus spp. and Streptococcus spp. that are Gram positive cocci are the main pathogens in several infections. Virulence factors such as usual and unusual surface proteins encoded by resistance genes are the main causes of pathogenesis. Multidrug-resistant pathogens that are the main causes of morbidity and mortality worldwide have the ability to synthesize a number of destructive enzymes encoded by resistance genes such as ?-lactamases. Resistant pathogens such as methicillin-resistant Staphylococcus aureus (MRSA), Streptococcus pneumoniae, Group A, and Group B Streptococcus have emerged throughout the world. To eliminate these resistant pathogens that cause untreatable, acute, and chronic infections, different new antimicrobials must be developed and used. The goal of this book is to provide the latest information about the above topics.